COMPRESSION STRENGTH AND WEIGHT OF CONCRETE F’C=210 KG/CM2AL REPLACING 7.5, 12.5 AND 22.5 % OF COARSE AGGREGATE WITH EXPANDED CLAY - Castro Torres, Yohana Nair; Mosqueira Moreno, Miguel Angel; Mosqueira Ramírez, Hermes Roberto (LACCEI, 2024)
In the investigation, it was determined how much influence replacing the coarse aggregate with expanded clay in 7.5, 12 and 22.5% influences the compressive strength and unit weight of a concrete of f’c=210 kg/cm2. The results were evaluated by comparing the standard sample with conventional aggregates and the samples with percentage of expanded clay. Uniaxial compressive strength was evaluated at ages 7, 14 and 28 days and unit weight in fresh and hardened state across 6”x12” specimens. According to the results, it is concluded that the unit weight in the fresh state decreases by 1.75%, 3.20% and 4.54%, respectively. And the unit weight in the hardened state after 28 days decreases by 2.89%, 3.91% and 4.91%, respectively. While the compressive strength at 28 days decreases by 6.66%, 12.34% and 14.36%, with respect to the standard sample, obtaining for all cases a structural concrete with a resistance greater than 210 Kg/cm2 and a unit weight of 2200 kg/m3. The objective of using artificial aggregates such as expanded clay is to provide greater homogeneity in the properties of concrete, adding new characteristics such as thermal and acoustic insulation, fire resistance, as well as reducing the volumetric weight, reducing the dimensions of the structural elements; providing harmony between structure and modern architecture. Peru and Cajamarca are located in an area of ​​high seismicity, according to Standard E030 [4].; Therefore, reducing the weight of the structure while maintaining the strength of the concrete allows the structure to behave better in the face of these external forces since the shear in the base caused by earthquakes is reduced. Having safer structures.